1992
DOI: 10.1038/356238a0
|View full text |Cite
|
Sign up to set email alerts
|

New mammalian chloride channel identified by expression cloning

Abstract: Ion channels selectively permeable to chloride ions regulate cell functions as diverse as excitability and control of cell volume. Using expression cloning techniques, a complementary DNA from an epithelial cell line has been isolated, sequenced and its putative structure examined by site-directed mutagenesis. This cDNA, encoding a 235-amino-acid protein, gave rise to a chloride-selective outward current when expressed in Xenopus oocytes. The expressed, outwardly rectifying chloride current was calcium-insensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
278
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(289 citation statements)
references
References 27 publications
10
278
1
Order By: Relevance
“…To identify the protein-protein interactions responsible for this regulation, we synthesized a biotin-tagged peptide corresponding to this sequence and used it as a probe to identify high affinity protein interactions dependent on this motif. From a high content, high density protein array derived from a redundant human brain cDNA expression library (37,200 clones) (43,44,46), we identified a number of novel, potential integrinregulating proteins (Fig. 1A).…”
Section: Kvgffkr-specific Binding Proteins Identified From High Densimentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the protein-protein interactions responsible for this regulation, we synthesized a biotin-tagged peptide corresponding to this sequence and used it as a probe to identify high affinity protein interactions dependent on this motif. From a high content, high density protein array derived from a redundant human brain cDNA expression library (37,200 clones) (43,44,46), we identified a number of novel, potential integrinregulating proteins (Fig. 1A).…”
Section: Kvgffkr-specific Binding Proteins Identified From High Densimentioning
confidence: 99%
“…However, hydrophobicity analysis indicates that ICln lacks the transmembrane helices necessary for channel-pore formation by most vertebrates. When expressed in Xenopus oocytes, it mediates a nucleotide-sensitive outwardly rectifying chloride channel closely resembling the biophysical properties of swelling-dependent chloride channels involved in regulation of cell volume decrease after cell swelling (36,37). It is found in the cytosol in cells-at-rest but is associated with the cell membrane following a hypotonic challenge.…”
mentioning
confidence: 99%
“…1 The roles of VSOR in cell volume regulation, proliferation, migration and cell death are well established, but its molecular identity has not fully been clarified until recently. 1,2 In the 1990s, several proteins, including P-glycoprotein, pI cln , and ClC-3, were proposed as molecular identities of VSOR, [3][4][5] but none of them has survived scrutiny. [6][7][8][9][10][11][12] In 2014, 2 research groups independently reported that the leucine-rich repeat containing 8A (LRRC8A), which has 4 transmembrane domains and a leucine-rich repeat (LRR) domain at the C-terminus, is a core factor of VSOR in human cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore I Cl(swell) is insensitive to changes in calcium concentrations (33). Despite much effort and several candidates, P-glycoprotein (P-gp) (42), pICln (30) and , none has stood the test of time, and the molecular identity of the channel responsible for I Cl(swell) and its mechanism of activation remain unknown. Extracellular acidification has been reported to both activate and inhibit anion channel activities in different cell types.…”
mentioning
confidence: 99%